Clinicohaematological study of anaemia in antenatal patients - Gupta, Veena; Sharma, Karishma; Chaurasia, Amrita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: According to WHO, approximately 75% of pregnant women in developing countries and 18% in developed countries are anaemic. In India prevalence of anaemia is reported to be 33%-89% and is one of the important causes of maternal morbidity and mortality. The present study was done with the objective to study the socio-demographic factors related to anemia and the distribution of different types of anaemia in antenatal patients. Methods: A prospective analytical study was done on 205 pregnant females who presented with anemia (Hb <11 gm/dl) in 1st, 2nd and early 3rd trimester (up to 30 weeks of gestation) in the department of obstetrics and gynecology of Swaroop Rani Nehru Hospital, Prayagraj from September 2017 to September 2018. Results: The rural background with lower socio-economic status comprised majority of the anemic patients (65.9%) with the major cause being iron deficiency anemia (68.8%). The patients mainly presented with anemia at late second or early third trimester (82.4%). Clinical signs like pallor, oedema and symptoms like palpitations and dyspnoea were more associated with severe anemia than mild and moderate anemia. Conclusions: Anemia prevention and prompt detection is the need of the hour with effective management. In India, major cause of anaemia are nutritional deficiencies which can be treated by proper diet and medications. The advises of routine iron supplementation during pregnancy, regardless of whether the mother is anemic or not, is strongly recommended by this study.